Benzodiazepines May Be Worse Than Opioids: Negative Medication Effects in Severe Chronic Pain. Issue 4 (April 2016) - Gauntlett-Gilbert, Jeremy; Gavriloff, Dimitri; Brook, Peter
Abstract : Objectives: Opioid prescription for noncancer pain is increasing in Europe and the United States. Research and guidance have focused on the potential for dependency and medical side effects with high doses. In contrast, benzodiazepines have received little attention in the chronic pain literature, despite evidence for dependency and cognitive impairment in long-term use. We aimed to examine the relationship between these classes of medication use, mood, and functioning. Methods: This cross-sectional study included patients (N=229) with disabling chronic pain who were about to start intensive pain rehabilitation. They completed self-report measures of mood, functioning, and responses to pain. We examined each patient's medication use and calculated a single morphine equivalent (ME) dose per person, and a similar diazepam equivalent (DE) dose. We examined the relationship between drug dose, mood, and functioning. Results: Higher DE doses were associated with worse outcomes in most domains. Higher ME doses were more narrowly associated with worse functioning. There was no evidence for any benefit of these drugs; higher doses were not associated with less pain, fear, or disability. Higher ME doses were not more problematic, contrary to our predictions. The combination of opioids and benzodiazepines was associated with particularly poor outcomes for mood. Discussion: This study is the first to examine both opioid and benzodiazepine use together in chronic pain. We found the anticipated negative effects of opioid medication, and particularly consistent associations between benzodiazepine use and poor well-being. Future guidance on chronic pain prescription should focus on restricting benzodiazepine use.